Multi-channel photodissociation and XUV-induced charge transfer dynamics in strong-field-ionized methyl iodide studied with time-resolved recoil-frame covariance imaging. (25th February 2021) - Allum, Felix; Anders, Nils; Brouard, Mark; Bucksbaum, Philip; Burt, Michael; Downes-Ward, Briony; Grundmann, Sven; Harries, James; Ishimura, Yudai; Iwayama, Hiroshi; Kaiser, Leon; Kukk, Edwin; et al.
Abstract : The photodissociation dynamics of strong-field ionized methyl iodide were probed using intense extreme ultraviolet (XUV) radiation produced by the SPring-8 Angstrom Compact free electron LAser. Abstract : The photodissociation dynamics of strong-field ionized methyl iodide (CH3 I) were probed using intense extreme ultraviolet (XUV) radiation produced by the SPring-8 Angstrom Compact free electron LAser (SACLA). Strong-field ionization and subsequent fragmentation of CH3 I was initiated by an intense femtosecond infrared (IR) pulse. The ensuing fragmentation and charge transfer processes following multiple ionization by the XUV pulse at a range of pump–probe delays were followed in a multi-mass ion velocity-map imaging (VMI) experiment. Simultaneous imaging of a wide range of resultant ions allowed for additional insight into the complex dynamics by elucidating correlations between the momenta of different fragment ions using time-resolved recoil-frame covariance imaging analysis. The comprehensive picture of the photodynamics that can be extracted provides promising evidence that the techniques described here could be applied to study ultrafast photochemistry in a range of molecular systems at high count rates using state-of-the-art advanced light sources.